Urban areas and climate changes - a case study of the city of Castro, PR - Garcias, Carlos Mello; Silva, Consuelo Marques da (Risco - Journal of Architecture and Urbanism, 2011)
The methodology for this research is a is a case study, which object of study is the municipality of Castro, Paraná, and has the principal porpoise of evaluate the possible contributions of the urban area for the climate change, identifying them and making an estimative about their emissions. Besides that, this research counted on the application of a semi-structured questionnaire of assessment about the populations’ perceptions about spots climate changes. With the application of a semi-structured questionnaire was found that most people are aware of their impacts on the climate, including the effects already felt in the city, however, the minority acts to reduce these impacts.